2006
DOI: 10.1007/s11240-006-9159-2
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration-induced alterations in growth and osmotic potential of callus from six tepary bean lines varying in drought resistance

Abstract: Growth and osmotic potential of calli induced from leaf-and root-derived tissues of six tepary bean lines (Phaseolus acutifolius) varying in drought resistance were assessed in vitro after polyethylene glycol-induced (10%, PEG-10,000) dehydration. Calli of resistant teparies were characterized by low initial osmotic potential (w s ) and relative growth rate (RGR) on medium lacking PEG (-0.30 MPa). However, calli of both resistant and sensitive lines were similar in dry matter percent (DM). Presence of PEG in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…3" showed lowest leaf Ψs under water deficit condition. Interestingly, it was found that leaf Ψs of "Longdong" and "Xinjiang Daye" were significantly lower than that of the other three cultivars under the normal condition, indicating that their adaptability to drought may be stronger than the other cultivars, since the lower initial leaf Ψs means the stronger water retention capacity (Mohamed and Tawfik, 2006;Ma et al, 2012). The data of leaf relative water content (RWC) in this study support this point.…”
Section: Discussionsupporting
confidence: 71%
“…3" showed lowest leaf Ψs under water deficit condition. Interestingly, it was found that leaf Ψs of "Longdong" and "Xinjiang Daye" were significantly lower than that of the other three cultivars under the normal condition, indicating that their adaptability to drought may be stronger than the other cultivars, since the lower initial leaf Ψs means the stronger water retention capacity (Mohamed and Tawfik, 2006;Ma et al, 2012). The data of leaf relative water content (RWC) in this study support this point.…”
Section: Discussionsupporting
confidence: 71%
“…Osmotic potential was determined with an osmometer (030), using sap extracts from fresh calli tissues. Osmolarity was expressed as MPa using the formula ψ s = 0.00227 k, where k = osmolarity in mosmol kg −1 [ 104 ].…”
Section: Methodsmentioning
confidence: 99%
“…A plant's morphological and physiological traits can be altered as a kind of adaptation in response to drought. Some of the ways plants react to drought include shrinking their leaves, sealing their stomata, altering the proportion of their biomass that is found in their shoots and roots, and modifying their roots (47)(48)(49). In response to drought stress, legumes' root systems grow and are distributed in ways that optimize their ability to survive (50, 51).…”
Section: Problems Related To Production and Climate Resilient Featuresmentioning
confidence: 99%